PENGARUH RASIO KESEHATAN BANK TERHADAP VOLUME PEMBIAYAAN BANK UMUM SYARIAH DI INDONESIA - Andriyanto, Irsad; Prastika, Aprilia Inge (MALIA: Journal of Islamic Banking and Finance, 2018)
This research aimed to analyze the effect of financial ratios on financing successfully channeled by Sharia Commercial Banks in Indonesia in 2015- 2018. The bank's ratio is measured through CAMELS ratios (Capital, Asset Quality, Management, Earning, Liquidity, Sensitivity to Market Risk) for each aspect. Capital aspects are measured using the Capital Adequacy Ratio (CAR), asset quality (Asset Quality) is measured using Non Performing Financing (NPF), profitability (Earning) is measured using Return on Assets (ROA) and Operational Expenses to Operating Revenues (BOPO ), and liquidity (Liquidity) is measured using Financing to Deposit Ratio (FDR). The samples are 13 Sharia Commercial Banks with the observation period from January 2015 till May 2018. The data obtained through Sharia Banking Statistics (SPS) are then processed by multiple linear regression analysis. The results showed that the NPF and BOPO had a negative effect on the financing volume of sharia commercial banks, while ROA had a positive effect. In other way, the CAR and FDR have no significant effect on the financing volume of sharia commercial bank. This is because the capital is used to cover troubled financing and to maintain public trust